Perlindungan Konsumen Muslim di Marketplace: Urgensi Transparansi Sertifikat Halal Digital (Studi pada Shopee) - Nanda Misbahul Humam; Fathurohman; Ainul Yaqin; Rohman Maulana (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2025)
The rapid growth of digital marketplaces demands assurance of product halalness for Muslim consumers. However, many products on platforms such as Shopee still lack clear information regarding their halal status. This study aims to analyze the guarantee of halal products in marketplaces and Shopee’s policy related to the transparency of digital halal certification. This research employs a normative juridical method using library research, focusing on legal regulations and Shopee’s internal policies. The findings indicate that halal product assurance represents a form of legal protection for Muslim consumers, in line with the principles of honesty (shidq) and responsibility (amanah). Shopee has not yet implemented a specific verification mechanism for digital halal certificates, making transparency of halal information an urgent necessity to ensure Muslim consumer protection in the era of electronic commerce.